Determinants of diarrhea in children aged under five at the Bengo General Hospital, Angola - Brito, Miguel (2018)
Introduction - Diarrhea is an important cause of morbidity and mortality in children aged under five, especially in low income countries. It is often associated to gastrointestinal infections due to pathogenic agents as bacteria, viruses and parasites. The aim of this study was to investigate the most frequent etiological agents of diarrhea in children aged under five attending Bengo General Hospital, Angola. Materials and Methods - From September 2012 through December 2013, 344 children with diarrhea attending the hospital were included in the study. A questionnaire was filled in and weight and length/height were measured. Stool samples were collected in a sterilized container. Rotavirus and adenovirus were detected using rapid qualitative immunochromatographic assay, astrovirus was detected by a commercial ELISA assay. Microscopic detection of intestinal parasites was performed through direct examination with saline iodine and a concentration method using the Kit Parasitrap-System. Immunochromatographic rapid tests were used to detect Entamoeba spp. Giardia lamblia and Cryptosporidium spp. Bacterial agents were studied by applying a conventional solid selective culture for Salmonella spp. and Shigella spp., Campylobacter jejuni, and Escherichia coli. Results 61% of the children were underweight, 54.6% were stunted and 51.0% were wasted. There were more cases of diarrhea in the wet than the dry season (54.7% vs. 45.3%). An enteric pathogen was detected in 66.6% of stool samples. We found Cryptosporidium spp. (30.0%), rotavirus (25.1%), Giardia lamblia (21.6%), diarrhoeagenic Escherichia coli (6.3%), Ascaris lumbricoides (4.1%), adenovirus (3.8%), Strongyloides stercoralis (3.5%), astrovirus (2.6%), Hymenolepis nana (1.7%), Entamoeba histolytica/dispar (0.9%), Taenia spp. (0.6%), Trichuris trichiura (0.3%) and Entamoeba histolytica (0.3%). Infection by rotavirus and by Cryptosporidium spp. was more frequent in children aged under 12 months. No statistical association was observed between infectious agents and water sources, water treatment or latrine usage. Conclusions - This study demonstrates high rates of infection, particularly in children aged under 12 months, enhancing the importance of taking action targeting this age group. Since the rotavirus vaccine was only recently introduced, further studies are needed to evaluate its impact on diarrheal disease.